Efficiency and Bond Selectivity in Plasmon‐Induced Photochemistry. Issue 15 (6th June 2017) - Cortés, Emiliano
Abstract : Light‐induced chemical reactions on bulk metal surfaces have been explored for more than 50 years. Light absorption at the metal surface plays a key role in inducing photochemical transformations of adsorbed molecules. Our current ability to control both the absorption cross‐sections and the energy of absorbed light by metal plasmonic nanoparticles opens new pathways for the manipulation of photochemical reactions. Physical phenomena associated with the localized surface plasmon resonances, such as energetic surface states and intensified electric fields, force us to revisit our traditional understanding of photochemical reactions at metal surfaces. Long standing goals in the field – such as bond selectivity and increased efficiency of photocatalytic processes – might now be achievable, assisted by plasmonic nanoparticles. This Progress Report intends to examine some of the elementary concepts and mechanisms behind these processes in the context of the most recent advancements in the fields of plasmonic‐assisted chemistry, charge transfer at the nanoscale, and surface photochemistry. Abstract : Plasmon‐induced photochemistry might allow us to perform bond‐selective reactions and to increase efficiency in light‐into‐chemical energy conversion processes. Metal nanoparticles, plasmon resonances, and metal–molecule interactions can be tuned and engineered with a high degree of control thus allowing unprecedented manipulation of the photochemical reaction pathways.